Survey of Economic and Social Developments in the ESCWA Region 2005-2006 - United Nations Economic; Social Commission for Western Asia (United Nations, 2008)
This annual Survey reviews economic and social trends in the Economic and Social Commission for Western Asia (ESCWA) region. It evaluates the region’s performance in areas such as economic development, population growth, health conditions, education and gender affairs. This year’s Survey warns that the impact from the current oil-boom on region-wide development remains below potential because of comparatively low levels of economic integration and sub-optimal macroeconomic structures in most UN-ESCWA member countries. The Survey emphasizes that in an area so rich in resources, a change could be readily achieved in a more regionally-integrative and tension-defused environment, with an economic policy centred on regional cooperation, investment facilitation and job creation.